Ulster Sectarianism and the Lessons of South Asian Historiography - Farrell, Sean (History compass, 2010)
In recent years, both Irish historians and literary scholars have paid much greater attention to the many parallels, linkages and disjunctures between Ireland and India. Unfortunately, this work has failed to examine the striking parallels between the construction and operation of sectarianism and sectarian violence in nineteenth-century Ulster and communalism and related violence in early twentieth-century India. Looking closely at how these issues have been treated in both historiographies, I argue that there are striking parallels, as both Irish and Indian/Pakistani historians have struggled with the dictates of postcolonial nationalism, moving from reductionist binary assumptions about the nature of societal division to what I term the ‘consensus of complex avoidance.’ Irish historians, however, have much to learn from their South Asian counterparts, who have moved beyond such sterile consensus in recent years, producing works of great sophistication and insight. Above all, these scholars have treated communalism as a complex historical subject; a contingent and ever shifting ideology that often overlaps and co-exists with seemingly contradictory notions of class and caste. This raises significant questions about the consensus of complex avoidance and the article closes by calling for Irish historians to revisit their assumptions about the study of Ulster sectarianism.